2009
DOI: 10.1111/j.1467-6486.2008.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Measures for Dealing with Competence and Integrity Violations of Interorganizational Trust at the Corporate and Operating Levels of Organizational Hierarchy

Abstract: We examine how partners in an interorganizational relationship can repair violated trust, and if that is impossible, how they can preserve the collaborative relationship. We also consider under what circumstances exit from the relationship is the only viable option. We propose that the effectiveness of legalistic and non-legalistic measures in response to a trust violation is a function of the hierarchical level at which the violation occurred (corporate vs. operating), the character of the violation (competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 79 publications
1
51
0
Order By: Relevance
“…This would suggest that the cultural-cognitive and normative elements make stronger contributions to MNE heterogeneity. Normative and cognitive forces may be more permeable than commonly thought, but possibly for worse rather than better, as illustrated by research on trust (see Janowicz-Panjaitan and Krishnan, 2009;Krishnan, Martin, and Noorderhaven, 2006). That is because these institutions also differ in the extent to which they need to be engaged and can be expected to respond, such that a strategically managed firm will deal differently with (partly) endogenous and strictly exogenous aspects of the local environment Martin, 2006, 2010).…”
Section: Toward a Theory Of Institutional Competitive Advantagementioning
confidence: 99%
“…This would suggest that the cultural-cognitive and normative elements make stronger contributions to MNE heterogeneity. Normative and cognitive forces may be more permeable than commonly thought, but possibly for worse rather than better, as illustrated by research on trust (see Janowicz-Panjaitan and Krishnan, 2009;Krishnan, Martin, and Noorderhaven, 2006). That is because these institutions also differ in the extent to which they need to be engaged and can be expected to respond, such that a strategically managed firm will deal differently with (partly) endogenous and strictly exogenous aspects of the local environment Martin, 2006, 2010).…”
Section: Toward a Theory Of Institutional Competitive Advantagementioning
confidence: 99%
“…Reychav and Weisberg (2009) found knowledge-sharing engagement to be positively associated with development of strong social relations. Other studies have found information exchange to be positively associated with trust (Hansen 1999;Janowicz-Panjaitan and Krishnan 2009;Kachra and White 2008). Also in a university setting, Li, Zhu, and Wang (2010) found knowledge-sharing activities to be associated with group cohesiveness.…”
Section: Discussionmentioning
confidence: 92%
“…This is typically caused by a perceived negative situation in which one or more parties perceive the conditions to be unacceptable, unethical, illegal, or simply as falling below their expectations (Weun et al, 2004;Janowicz-Panjaitan and Krishnan, 2009). This is typically caused by a perceived negative situation in which one or more parties perceive the conditions to be unacceptable, unethical, illegal, or simply as falling below their expectations (Weun et al, 2004;Janowicz-Panjaitan and Krishnan, 2009).…”
Section: Trust Violationmentioning
confidence: 99%